Knowledge and Attitudes Toward Cough Self-Medication among Parents of Toddlers - Murtia Fitriasari; Ovikariani Ovikariani; Truly Anggraini (Indonesian Journal of Global Health Research, 2026)
Cough is a common symptom in children and is frequently managed through self-medication. Limited parental knowledge may lead to inappropriate medicine selection, dosing errors, and potential adverse effects. To examine the levels of knowledge and attitudes and to analyse the association between knowledge level and attitudes towards cough self-medication among parents of toddlers in Parangjoro Hamlet, Grogol District, Sukoharjo Regency. A quantitative cross-sectional study was conducted among 99 parents of toddlers selected using purposive sampling. Data were collected using a validated and reliable questionnaire and analysed using univariate statistics and the Chi-square test. Most respondents had a good level of knowledge (70.71%), and 59.6% showed positive attitudes towards cough self-medication. There was a statistically significant association between knowledge level and attitudes (p=0.001). Higher knowledge was associated with more positive attitudes towards cough self-medication among parents of toddlers.